Incentive-Based Capital Requirements - Eufinger, Christian; Gill, Andrej (Management Science, 2017)
This paper proposes a new regulatory approach that implements capital requirements contingent on executive incentive schemes. We argue that excessive risk taking in the financial sector originates from the shareholder moral hazard created by government guarantees rather than from corporate governance failures within banks. The idea behind the proposed regulatory approach is thus that the more the compensation structure decouples the interests of bank managers from those of shareholders by curbing risk-taking incentives, the higher the leverage the bank is permitted to take on. Consequently, the risk-shifting incentives caused by government guarantees and the risk-mitigating incentives created by the compensation structure offset each other such that the manager chooses the socially efficient investment policy. This paper was accepted by Amit Seru, finance.